Psychometric properties of Quality-of-Life Index for Vietnamese women with breast cancer three weeks postmastectomy - Xuan Thi Nhu Ha; Sureeporn Thanasilp (Belitung Nursing Journal, 2021)
Background: The patient’s quality of life immediately after mastectomy usually receives less attention than the quality of life after three months, six months, or a year. It is because the focus is mainly on surgical complications. Many instruments measure the quality of life from three months onwards. Still, the quality-of-life instruments right after postmastectomy is not yet verified. Objective: This paper aimed to test the reliability and validity of the Quality-of-Life Index Vietnamese version (QOLI-V) in Vietnamese women with breast cancer three weeks postmastectomy. Methods: The descriptive cross-sectional study was designed to analyze the psychometric properties of a Vietnamese version of the modified Quality of Life Index. The modified process was conducted after granting permission from the original authors. The content validity of the modified index was examined by five experts. Brislin’s model was used for the translation process. The 26-item QOLI-V was tested in 265 patients with breast cancer stage II three weeks postmastectomy who expected to have a poorer quality of life score. The reliability of the index was measured by Cronbach's alpha. The construct validity was examined using confirmatory factor analysis (CFA). Result: The content validity index results showed that the lowest I-CVI was .80 and the highest was 1.00. S-CVI/Ave was 0.95, and S-CVI/UA was 0.76. The Cronbach's alpha of QOLI-V was .84, which was considered acceptable. Most of the 26 items featured the correct item-total correlation of .30 to .60. There were only two items correlated with the total scale at .18, and the item with the lowest correlation (.06) was deleted from the item set.  The CFA of model 1 with 26 items was not an ideal fit with the data, with Chi-Square/df = 2.15, CFI =.815, GFI = .853, TLI=.792 RMSEA =.066. After deleted an item #general quality of life, and the CFA of model 2 was conducted on the 25-item index. The final result indicated the improvement of the model fit, with Chi-Square/df =2.26, CFI=.852, GFI=.814, TLI=.790, RMSEA=.069. Conclusion: The 25-item QOLI-V version is considered valid and reliable to measure the quality of life of Vietnamese women with breast cancer three weeks postmastectomy. Nurses and midwives could use this instrument to measure the quality of life of the patients, and the patients could use it for self-assessment.